Investigating social media-based brand communities engagement’s motives and evangelistic tendencies for football sport’s fans - Fawzy Mohamed, Dr Mahmoud; Mohamed Abdelshafy, Menna; Yehia Ebeid, Ahmed (International Journal of Scientific Research and Management (IJSRM), 2023)
This study aims to investigate variables that motive brand community engagement. Moreover, explore the mediating role of brand evangelism between brand community engagement and brand defense. The data was collected using quantitative research through an online questionnaire-based survey from 217 active members of certain social media brand communities (SMBCs) which are Facebook and Whatsapp. I chose them because they provide similar functionality. The data was analyzed by using regression analysis. Facebook; for example, adopting instant messaging (IM) features similar to those found in Whatsapp however, the two tools of social media provide different social practices, resulting in different user experiences with the same functionality. Thus, the current research adapted these two tools to add richness to data collection. Respondents are a variety of university students and more than 50 different occupations. The data was analyzed by using multiple regression analysis. The research findings provide a comprehensive analysis of user perceptions and engagement within an entertainment platform across eight dimensions. Users generally hold favorable opinions of the platform, with high ratings for entertainment and information, while self-discovery offers opportunities for improvement. Reliability analysis indicates strong internal consistency among measured items, enhancing data trustworthiness. The correlation matrix underscores significant relationships among dimensions, highlighting their interconnectedness. Kaiser-Meyer-Olkin and Bartlett's Test supports data suitability. Communalities reveal variable significance through PCA. Regression analysis demonstrates the model's effectiveness in explaining engagement variance. Additionally, mediation analysis emphasizes the direct effects of engagement on brand defense, and the indirect one via brand evangelism, contributing to a deeper understanding of user experiences on the platform.